The effect of Plant by-products on liver functions and plasma glucose in rats fed a high fat diet induced obesity. - سارة أحمد محمد السيد أحمد (Faculty of Education - Port Said University, 2016)
The present study examined the effects of dietary supplementation of four plant by-products (potato peel, cauliflower leaves, onion skin, and mango peel) in therapeutic nutrition through evaluating the effectiveness of these plant by-products mixed in bread in modulating obesity parameters using obese rat model.            All (35) adult male rats, 150 ±10g, rats were fed on basal diet for one week before starting the experiment for acclimatization. After one week period, the rats were divided into two main groups, the first group: Group(-) , 5 rats still fed on basal diet and the other main group (30 rats) was feed with diet-induced obesity (DIO) for 4 weeks which classified into sex sub groups as follow: Group (+): fed on DIO as a positive control Group (PPP), fed on DIO containing 5 % PPP, Group (CLP), fed on DIO containing 5 % CLP ,Group (ROSP), fed on DIO containing 5 % ROSP, Group (MPP), fed on DIO containing 5 % MPP, Group (Mixture): fed on DIO containing 5 % mixture, PPP +  CLP+ ROSP + MPP by equal parts.          At the end of the experimental period (4 weeks) blood was collected then glucose and liver and functions were determined in the serum. The results indicated that supplementation of the rat diets with 5% w/w by PPP, CLP, ROSP, MPP and their mixture induced significant decreasing on serum glucose concentrations liver AST, ALT and ALP activities. * PPP, potato peel powder, CLP; cauliflower leaves powder; ROSP, red onion skin powder;   MPP, mango peel powder and Mixture, PPP + CLP+ ROSP + MPP by equal parts.